Nitrative Modification of Caveolin-3: A Novel Mechanism of Cardiac Insulin Resistance and a Potential Therapeutic Target Against Ischemic Heart Failure in Prediabetic Animals. Issue 15 (8th March 2023) - Meng, Zhijun; Zhang, Zhen; Zhao, Jianli; Liu, Caihong; Yao, Peng; Zhang, Ling; Xie, Dina; Lau, Wayne Bond; Tsukuda, Jumpei; Christopher, Theodore A.; Lopez, Bernard; Zhu, Di; et al.
Abstract : Background: Myocardial insulin resistance is a hallmark of diabetic cardiac injury. However, the underlying molecular mechanisms remain unclear. Recent studies demonstrate that the diabetic heart is resistant to other cardioprotective interventions, including adiponectin and preconditioning. The "universal" resistance to multiple therapeutic interventions suggests impairment of the requisite molecule(s) involved in broad prosurvival signaling cascades. Cav (Caveolin) is a scaffolding protein coordinating transmembrane signaling transduction. However, the role of Cav3 in diabetic impairment of cardiac protective signaling and diabetic ischemic heart failure is unknown. Methods: Wild-type and gene-manipulated mice were fed a normal diet or high-fat diet for 2 to 12 weeks and subjected to myocardial ischemia and reperfusion. Insulin cardioprotection was determined. Results: Compared with the normal diet group, the cardioprotective effect of insulin was significantly blunted as early as 4 weeks of high-fat diet feeding (prediabetes), a time point where expression levels of insulin-signaling molecules remained unchanged. However, Cav3/insulin receptor-β complex formation was significantly reduced. Among multiple posttranslational modifications altering protein/protein interaction, Cav3 (not insulin receptor-β) tyrosine nitration is prominent in the prediabetic heart. Treatment of cardiomyocytes with 5-amino-3-(4-morpholinyl)-1, 2, 3-oxadiazolium chloride reduced the signalsome complex and blocked insulin transmembrane signaling. Mass spectrometry identified Tyr 73 as the Cav3 nitration site. Phenylalanine substitution of Tyr 73 (Cav3 Y73F ) abolished 5-amino-3-(4-morpholinyl)-1, 2, 3-oxadiazolium chloride–induced Cav3 nitration, restored Cav3/insulin receptor-β complex, and rescued insulin transmembrane signaling. It is most important that adeno-associated virus 9–mediated cardiomyocyte-specific Cav3 Y73F reexpression blocked high-fat diet–induced Cav3 nitration, preserved Cav3 signalsome integrity, restored transmembrane signaling, and rescued insulin-protective action against ischemic heart failure. Last, diabetic nitrative modification of Cav3 at Tyr 73 also reduced Cav3/AdipoR1 complex formation and blocked adiponectin cardioprotective signaling. Conclusions: Nitration of Cav3 at Tyr 73 and resultant signal complex dissociation results in cardiac insulin/adiponectin resistance in the prediabetic heart, contributing to ischemic heart failure progression. Early interventions preserving Cav3-centered signalsome integrity is an effective novel strategy against diabetic exacerbation of ischemic heart failure.